FRI0505 Long-Term Efficacy and Safety of Mycophenolate Mofetil in Childhood Primary Central Nervous System Vasculitis. (9th June 2015) - Brambilla, A.; Cosi, A.; Rosati, A.; Guerrini, R.; Cimaz, R.; Simonini, G.
Abstract : Background: Childhood primary central nervous system vasculitis (cPANCS) is an inflammatory brain disease targeting either small (angiography-negative) or medium-large (angiography-positive) central nervous system vessels. Vascular inflammation is reversible with proper immunosuppressant treatment, preventing disabling neurologic impairment. Objectives: To report efficacy and sustained remission in 4 children affected by cPANCS treated with MMF. Methods: Between December 2011 and August 2014, 4 patients (median age 77 months, range 9-165) were referred to our centre due to stroke symptoms associated to focal areas of acute ischemia at brain neuroimaging. Screening for thromboembolic and metabolic diseases was negative in all patients as well as complete cardiologic evaluation. Antiplatelet and anticoagulant treatments lead to transient clinical and radiological improvement. After a median period of 7 months (range 2-11) they showed clinical and/or radiologic relapse, with documented progression of vascular involvement at magnetic resonance angiography (MRA) or cerebral angiogram. Laboratory work up for infectious diseases, inflammatory and autoimmune conditions excluded secondary causes of central nervous system vasculitis, thus prompting the diagnosis of cPANCS. Methyl-prednisolone (30mg/kg for 3-5 days) was then started, followed by administration of oral Prednisone (1-2 mg/kg/day) and induction therapy with MMF (1000 mg/m 2 divided BID). Brain MRI controls have been performed every 3-6 months according clinical history and neurological evaluation. Results: Median period of MMF treatment was 18.8 months (range 3-27). Steroid tapering was started after 6 weeks from the beginning and complete discontinuation was achieved within 7-8 months in 3 out of 4 patients. One patient is still on steroid tapering. Periodic clinical examination, blood tests and MRA were performed with evidence of clinical and radiological improvement or, at least, stable findings. In all children, no relapse of cerebral vasculitis occurred during the follow-up period (median 19.8 months, range 5-29). No major side effects and/or drug-related adverse events were documented during the study period of treatment. Conclusions: Despite the restricted number of enrolled patients, we report efficacy, good tolerance along with persistent improvement and remission in children affected by cPANCS treated with MMF for up to 27 months. Disclosure of Interest: None declared